3-point block backward differentiation formulas for solving fuzzy differential equations - Ismail, Nurzeehan; Ibrahim, Zarina Bibi; Othman, Khairil Iskandar; Suleiman, Mohamed (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
In this paper, 3-point Block Backward Differentiation Formulas (3BBDF) is used for the numerical solution of Fuzzy Differential Equations (FDEs). Implementation of 3BBDF using Newton iteration is discussed. Numerical results obtained by the 3BBDF are presented and compared with the Modified Simpson method to illustrate the ability of the 3BBDF method for solving FDEs.